Financial Feasibility Analysis of Cenderawasih University Teaching Hospital Building Project - Muhamad Suliswanto; Dewi Ana Rusim; Apolo Safanpo (International Journal of Social Service and Research, 2023)
Acceleration of development in the 3T (Forefront, Outermost and Disadvantaged) areas is the main goal of the government in supporting economic equality and educational services in the land of Papua. So that Cenderawasih University as an extension of the government plans to build a Teaching Hospital to support the activities and development of Cenderawasih University graduates and carry out health services, research and community services. In this study to analyze the feasibility of this teaching hospital project using the NPV (Net Preset Value), BCR (Benefit Cost Ratio), IRR (Internal Rate Ratio), BEP (Break Even Point) and sensitivity analysis methods to determine whether the hospital The project is feasible or not feasible but it is hoped that the results of the analysis are positive.